Employment Law Reform: A Responsive and Participatory Approach to Create Laws that Achieve Social Justice - Mardonius Irawan Profianto; Faisal Santiago (Ridwan Institute, 2026)
Social justice is a key measure of whether Indonesia, as a welfare state, is capable of realizing true prosperity. The numerous judicial reviews of the Employment Cluster of the Job Creation Law, both the 2020 Job Creation Law and the 2023 Job Creation Law, reflect public doubts about the country's ability to achieve social justice. This paper reviews the Job Creation Law from a social justice perspective and then explains how responsive law achieves social justice. The research method is normative juridical, using both a statutory and conceptual approach. The secondary data sources consist of primary legal materials, various legal regulations and court decisions, and secondary legal materials, namely books and articles related to the research. The results of the study indicate that the Job Creation Law, specifically the Employment Cluster, has shortcomings in terms of social justice. The numerous judicial reviews from the public are due to the lack of public participation and transparency in the law-making process, and are considered to not provide social justice for applicants, most of whom are workers. Responsive law offers advantages that can address the shortcomings of the Job Creation Law, as it better accommodates the needs and aspirations of the community and brings the desired benefits to realize social justice by prioritizing the principles of openness, efficiency and effectiveness, clarity of objectives, and meaningful community participation.